Double cross ebook Double cross. - Gibbs, Stuart (The Last Musketeer, 2013)
The past, present, and future are all at stake in this final book in the thrilling time travel adventure trilogy from New York Times bestselling Charlie Thorne and Spy School author Stuart Gibbs. Greg Rich should feel invincible. After all, he's traveled through time, become one of the legendary Musketeers, and—most recently—prevented the Spanish army from attacking Paris. Instead, he and his friends are languishing in prison, having fallen into a trap set by Milady and the Prince of Condé. But Greg didn't come to the seventeenth century to sit in a jail cell and await execution. He, Aramis, Athos, and Porthos need to get to King Louis, who is in immediate danger of being overthrown by the scheming prince. To save the king and history itself, the boys must break out of prison, defend Louis, and return Greg and his parents to the twenty-first century before it's too late. Don't miss the thrilling Last Musketeer trilogy from Spy School author Stuart Gibbs!